Bone-Targeting Liposome-Encapsulated Salvianic Acid A Improves Nonunion Healing Through the Regulation of HDAC3-Mediated Endochondral Ossification - Zhou L; Wu H; Gao X; Zheng X; Chen H; Li H; Peng J; Liang W; Wang W; Qiu Z; Udduttula A; Wu K; et al. (Dove Medical Press, 2020)
Limin Zhou,1,* Haojun Wu,2,* Xiang Gao,2,* Xiaoyan Zheng,1 Hang Chen,2 Hailong Li,1 Jun Peng,1 Weichong Liang,1 Wenxing Wang,1 Zuocheng Qiu,3 Anjaneyulu Udduttula,3 Kefeng Wu,1 Lin Li,4 Yuyu Liu,1 Yanzhi Liu1,3 1Guangdong Key Laboratory for Research and Development of Natural Drugs, Department of Pharmacology, Guangdong Medical University, Zhanjiang, Guangdong 524023, People’s Republic of China; 2Department of Orthopaedics, Stem Cell Research and Cellular Therapy Center, The Affiliated Hospital of Guangdong Medical University, Zhanjiang, Guangdong 524001, People’s Republic of China; 3Translational Medicine R&D Center, Institute of Biomedical and Health Engineering, Shenzhen Institutes of Advanced Technology, Chinese Academy of Sciences, Shenzhen 518055, People’s Republic of China; 4School of Pharmaceutical Sciences, Southern Medical University, Guangzhou 510515, Guangdong Province, People’s Republic of China*These authors contributed equally to this workCorrespondence : Yanzhi Liu Email liuyanzhi02@163.comYuyu Liu Email liuyuyu77@163.comAim: Nonunion is a major complication in fracture repair and remains a challenge in orthopaedics and trauma surgery. In this study, we aimed to evaluate the effectiveness of treatment of nonunion with a large radial defect using a bone-targeting liposome-encapsulated salvianic acid A (SAA-BTL)-incorporated collagen sponge and further elucidate whether the effects were closely related to histone deacetylase 3 (HDAC 3)-mediated endochondral ossification in nonunion healing process.Methods: Fifteen New Zealand female rabbits were randomly divided into three groups. Segmental radius critical size defects (15 mm) were created via surgery on both the forelimbs of the rabbits. The SAA-BTL/SAA/saline-incorporated collagen sponges were implanted into the defects in the three groups, respectively, for four weeks of treatment. X-ray imaging, micro-computed tomography (CT) analysis, histology, and immunofluorescence analysis (HDAC3, collagen II, VEGFA, and osteocalcin) were performed to determine the effects of the treatments. In addition, a short interfering RNA was applied to induce HDAC3 knockdown in the chondrogenic cell line ATDC5 to investigate the roles of HDAC3 and SAA intervention in endochondral ossification in nonunion healing.Results: X-ray imaging and micro-CT results revealed that SAA-BTL-incorporated collagen sponges significantly stimulated bone formation in the nonunion defect rabbit model. Furthermore, immunofluorescence double staining and histology analysis confirmed that SAA-BTL significantly increased the expression of P-HDAC3, collagen II, RUNX2, VEGFA, and osteocalcin in vivo; accelerated endochondral ossification turnover from cartilage to bone; and promoted long bone healing of nonunion defects. ATDC5 cells knocked down for HDAC3 showed significantly decreased expression of HDAC3, which resulted in reduced expression of chondrogenesis, osteogenesis, and angiogenesis biomarker genes (Sox9, Col10a1, VEGFA, RUNX2, and Col1a1), and increased expression of extracellular matrix degradation marker (MMP13). SAA treatment reversed these effects in the HDAC3 knockdown cell model.Conclusion: SAA-BTL can improve nonunion healing through the regulation of HDAC3-mediated endochondral ossification.Keywords: nonunion, fracture, HDAC3, endochondral ossification, bone-targeting liposome, salvianic acid A